Consultants' personal characteristics in the clinical setting influence on residents' attitude to learning - Clemente-Morada, Edna Sarah
A number of studies have attempted to identify the characteristics of the attending physician that influence learning in the clinical setting. The authors of these studies mentioned especially the clinical competence and teaching skill components in facilitating learning. Still, others have identified some characteristics that are beyond academic and clinical competencies. This study sought to focus on personal characteristics. Its aim was to identify the different personal characteristics of consultants which can influence attitude to learning of residents. It also aimed to determine which of these consultants' characteristics are facilitative or inhibitive to learning. A demographic profile of the residents included in the study was gathered. Ten selected residents from The Medical City participated in two focus group discussions (FGD) on how personal characteristics of consultants have affected their learning. Development of a questionnaire ensued after the FGD. It was directly administered to all 106 residents of the different departments of The Medical City after its pilot testing. Response rate was 74%. Frequency distributions and measures of central tendency were utilized to analyze the data using the Statistical Package for Social Sciences (SPSS). Profile of respondents included mostly female resident-trainees, single, in their late twenties, university hospital graduates, fresh graduates (within the last 5 years), mostly finished internship at The Medical City and mostly in the first year residency. This study revealed that the facilitative characteristics of consultants influencing residents to learn are competence, approachability, respectful attitude, confidence, orderliness and caring attitude. In contrast those that appeared to be inhibitive are temper/mood, discouraging attitude, inconsistency, ingratitude, anxiety, and impulsiveness. The study concludes that residents' learning is influenced by consultants' personal traits or characteristics. The ability of consultants to serve as role models to their trainees is imperative. The consultants must be aware of the influence they exert as role models and should fully take advantage of this particular perception in their interaction with residents. It is recommended that a correlational study with resident's learning style and learning environment as variables be undertaken so as to fully comprehend residents' responses. Also, it is recommended that reliability and validity of the questionnaire be further tested. Lastly, a multi-center study can be undertaken to augment sample size and establish trends regarding the subject matter.